Well-designed NiS/CdS nanoparticles heterojunction for efficient visible-light photocatalytic H2 evolution. (22nd March 2022) - Zhang, Kejie; Mou, Zhen; Cao, Shihai; Wu, Shuang; Xu, Xueting; Li, Caolong
Abstract: Heterojunction photocatalysts based on semiconducting nanoparticles show excellent performance in many photocatalytic reactions. In this study, 0D/0D heterojunction photocatalysts containing CdS and NiS nanoparticles (NPs) were successfully synthesized by a chemical precipitation method. The NiS NPs were grown in situ on CdS NPs, ensuring intimate contact between the semiconductors and improving the separation efficiency of hole-electron pairs. The obtained NiS/CdS composite delivered a photocatalytic H2 evolution rate (7.49 mmol h −1 g −1 ), which was 39.42 times as high as that of pure CdS (0.19 mmol h −1 g −1 ). This study demonstrates the advantages of 0D/0D heterojunction photocatalysts for visible light-driven photocatalytic hydrogen production. Highlights: 0D/0D NiS/CdS heterojunction were successfully synthesized by a novel method. Photocatalytic activity of NiS/CdS-X was related to the crystallization time of CdS. NiS/CdS-90 showed high catalytic activity and stability for hydrogen evolution. The possible mechanism for enhanced photocatalytic activity was proposed.